Internet Fraud: Information for Teachers and Students - Nkotagu, Gabriel Hudson (Journal of International Students, 2011)
Internet fraud takes a number of forms with the responsible individuals changing tactics rapidly to avoid detection. The perpetrators rely on telemarketing, emails, as well as presenting themselves personally to unsuspecting people. The evolution of internet marketing as well as ecommerce and the ease of connectivity create increasing opportunities for fraudsters while at the same time placing more unsuspecting internet users at risk of falling prey to these schemes. There exists a thriving economy online with large sums of money changing hands online. It is therefore important for any internet user to easily identify when they are exposed to internet fraud schemes and as such avoid being a victim.